Morphological diversity of Indian jujube (Ziziphus mauritiana) in Sumbawa Island, West Nusa Tenggara, Indonesia - ALUH NIKMATULLAH; IHLANA NAIRFANA; SUPRAYANTI MARTIA DEWI; MUHAMMAD SARJAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nikmatullah A, Nairfana I, Dewi SM, Sarjan M. 2023. Morphological diversity of Indian jujube (Ziziphus mauritiana) in Sumbawa Island, West Nusa Tenggara, Indonesia. Biodiversitas 24: 4597-4608. Ziziphus mauritiana Lam. (Indian jujube or Bidara) is an evergreen shrub or small tree tolerant to drought, salinity, and high-temperature stress with various ethnobotanical and ecological values. However, minimal information is available on its diversity in Indonesia. The current study aims to assess the morphological diversity of Z. mauritiana accessions collected from 18 locations in Sumbawa Island, Indonesia. The plant's qualitative and quantitative morphological attributes were collected, including size, L/W ratio and color of leaf and fruit, length, and occurrence of spine and stem surface. The results revealed significant differences in some observed characters among the accessions. Petiole length varied from 0.6 to 1.4 cm, leaf length ranged from 2.9 to 5.0 cm, leaf width ranged from 2.6 to 4.2 cm, and leaf L/W ratio was 1.07 to 1.46. All samples of Z. mauritiana in Sumbawa Island had a spine that occurred evenly in every node, ranging from 0.1 to 1.0 cm. Most accessions had single spinal per node except two accessions, which had double horn-shaped spines in each node. The quantitative characters for fruits also varied, either orbicular or oblong. The fruit length ranged from 1.2 to 1.9 cm, the fruit width varied between 1.1 to 1.8 cm, and the fruit L/W ratio was between 1.0 and 1.2. There were also morphological differences in leaf color, fruit color, shape, and taste (sweet, sour, or bitter). The finding suggests some degree of morphological diversity of Z. mauritiana in Sumbawa, as shown by quantitative and qualitative attributes of the leaf, thorn, and fruit.